Results of selective treatment of spina bifida cystica. - Lorber, J (1981)
The results of selective treatment in 120 infants with open spina bifida, admitted between May 1971 and December 1976, were prospectively studied. Seventy-one infants had adverse criteria at birth and were not treated. They all died, more than 90% of them within 6 months of birth. Seven had meningocele. All were treated and survived without handicap. Forty-two infants with myelomeningocele were actively treated. Thirty-six survive at follow-up after 3 to 9 years. The quality of survival is much better than when selection was not used but 8 children have moderate or severe handicaps. The parents were fully informed and consulted at every decision-making step; they fully supported the principle of selection and the action taken on behalf of their own child.